Drifting Sand Hazard and Its Control in North-west Arid China - Songqiao, Zhao (Annals of Arid Zone, 2016)
The paper deals with the magnitude and the extent of the shifting sand hazard in the north-west arid China. The aspects covered are: physical processes of drifting sand, sources of sand, wind regime causing the sand drift, sand drift hazard in relation to bioclimatic zones and land types, and finally the strategies for combating drifting sand hazard according to physical features and climatic zonation of the north west arid China.